Weak - form efficient market hypothesis versus bahavioural finance: A different perspective drawn from the Malaysian stock market - Lim, Kian Ping; Liew, Venus Khim-Sen; Wong, Hock Tsen (Universiti Malaysia Sabah, 2005)
This study utilies the windowed testing procedure of Hinich & Patterson (1995) to examine the data generating process of KLCI return series.Unlike previous studies, the present one relates the evidence to the weak-form Efficient Market Hypothesis (EMH) and behavioural finance, with the hope of offering some plausible explanations to the controversy existing between these two camps. Our econometrics results indicate that linear and non-linear dependencies play a significant role in the underlying data generating process. However, these dependencies are not stable as the results reveal that they are episodic and transient in nature. Along the line of our interpretations, we are able to offer some plausible explanations as to why weak-form EMH generally holds in the Malaysian stock market, though the presence of linear and nonlinear dependencies implies the potential of returns predictability. Specifically, these significant dependencies show up at random intervals for a brief period of time but then disappear again before they can be exploited by investors. Looking from a micro perspective, we are able to rationalise the co-existence of weak-form EMH and behavioural finance in the Malaysian stock market when the statistical properties of random walk, linear and non-linear dependencies, which also co-exist in the time domain, are interpreted in the framework of information arrival and market reactions to that information.